Tamoxifen and its active metabolites inhibit dopamine transporter function independently of the estrogen receptors. Issue 1 (14th February 2017) - Mikelman, Sarah R.; Guptaroy, Bipasha; Gnegy, Margaret E.
Abstract: As one of the primary mechanisms by which dopamine signaling is regulated, the dopamine transporter (DAT) is an attractive pharmacological target for the treatment of diseases based in dopaminergic dysfunction. In this work we demonstrate for the first time that the commonly prescribed breast cancer therapeutic tamoxifen and its major metabolites, 4‐hydroxytamoxifen and endoxifen, inhibit DAT function. Tamoxifen inhibits [ 3 H]dopamine uptake into human DAT (hDAT)‐N2A cells via an uncompetitive or mixed mechanism. Endoxifen, an active metabolite of tamoxifen, asymmetrically inhibits DAT function in hDAT‐N2A cells, showing a preference for the inhibition of amphetamine‐stimulated dopamine efflux as compared to dopamine uptake. Importantly, we demonstrate that the effects of tamoxifen and its metabolites on the DAT occur independently of its activity as selective estrogen receptor modulators. This work suggests that tamoxifen is inhibiting DAT function through a previously unidentified mechanism. Abstract : We demonstrate for the first time that the breast cancer therapeutic tamoxifen and its major metabolites, 4‐hydroxytamoxifen and endoxifen, inhibit dopamine transporter function, possibly through an allosteric interaction with the transporter. We demonstrate that these effects occur independently of any activity at the estrogen receptors. This work suggests a previously unidentified mechanism for tamoxifen that may have clinical implications.